The process of learning and teaching in supplemental instruction groups at Rhodes University - Vorster, Jo-Anne Elizabeth (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
This thesis investigates the process of peer collaborative learning in three Supplemental Instruction (SI) groups at Rhodes University. The roles of the SI leader, the students and the task in the peer-collaborative learning-teaching process were researched. The research is rooted in sociocultural theories of learning and development. The notion of activity is thus central to this investigation. The tasks, goals and interactions in the SI sessions were analysed in order to arrive at an understanding of the process of learning-teaching in each of the three SI sessions. A method of analysis devised by Van Vlaenderen to study the process of everyday cognition in the problem solving activities of community activists (1997) was adapted for this study. The method of analysis was used to study the interaction processes of participants in the SI groups. Each interaction between the SI participants was broken into its constituent parts and labeled in terms of the goals of the interactions in relation to the preceding interaction or operation, the task or subtask under discussion, and the SI session as a whole. Data from the analysis of the activity were quantified in order to assess the quality of the learning-teaching process. A qualitative analysis of the patterns of mediation was used in conjunction with the quantified data of interaction patterns to draw conclusions about the nature of the peer collaborative learning-teaching process in the three SI sessions. The research findings indicate that the nature of the SI task is crucial; students in SI need to be able and willing to participate; and the facilitation style of the SI leader plays a role in determining the quality of the activity in the SI session. The thesis explicates learning-teaching activity that results in higher order learning.
Keywords: Group work in education; Team learning approach in education; College teaching -- South Africa